Mineralogical controls on metamorphic fluid flow in metabasaltic sills from Islay, Scotland - Kleine, Barbara I.; Pitcairn, Iain K.; Skelton, Alasdair D.L. (Lithos, 2016)
In this study we show that mineralogy was the primary control of metamorphic fluid flow in the well-studied metabasaltic sills in the SW Scottish Highlands. Here, basaltic sills have been partially carbonated by H2O-CO2 fluids at greenschist facies conditions. This has led to mineral zonation with carbonate-poor sill interiors separated from carbonate-rich sill margins by reaction fronts. Although deformation set the stage for metamorphic fluid flow in the SW Scottish Highlands by causing the preferred alignment of mineral grains, metamorphic fluid flow was not coupled with active deformation but occurred later utilizing the pre-existing mineral alignment as a means of accessing the sill interiors. The sills which were studied were partially carbonated with well-preserved reaction fronts. They were selected because (atypically for the SW Scottish Highlands) they are mineralogically heterogeneous making them ideal for a study of mineralogical controls of metamorphic fluid flow. Their mineralogical heterogeneity reflects chemical heterogeneity arising from magmatic flow differentiation and spilitization, which occurred before greenschist facies metamorphism. Magmatic flow differentiation resulted in parts of the sill containing large crystals with no preferred alignment. Large (up to 3 cm) plagioclase phenocrysts were concentrated in the sill interior whereas large (up to 1 cm) amphibole (after pyroxene) grains formed cumulate layers close to the sill margins. These large randomly oriented crystals were replaced by an interface-coupled dissolution-precipitation mechanism. Replacement is constant volume and with hydration and carbonation affecting the cores of these minerals while the rims are remained intact and unaltered. This finding points to intra-granular metamorphic fluid flow. In contrast inter-granular metamorphic fluid flow was facilitated by mineral alignment on different scales. Pre-metamorphic spilitization, produced layers of epidote called segregations, whereas regional deformation caused preferred alignment mainly of amphibole and chlorite. Epidote undergoes a series of volume changes during greenschist facies metamorphism. This created porosity which produced preferred pathways for metamorphic fluids affecting the advancement of fluid-driven reaction fronts. Preferred alignment of amphibole and chlorite also affected the advancement of reaction fronts. In this case, fluid flow was preferentially parallel to the foliation. In both cases, inter-granular metamorphic fluid flow utilized a pre-existing fabric albeit on different scales. These results show intra-granular metamorphic fluid flow in unfoliated rock and inter-granular metamorphic fluid flow in foliated rock. In both cases metamorphic fluid flow occurred after deformation controlled by pre-existing mineralogical heterogeneities, such as grain composition and shape anisotropy as well as preferred alignment of mineral grains.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Carbonation; Fluid flow mechanisms; Fluid-rock interaction; Greenschist facies metamorphism; Hydration; Spilitization